Mesoscale eddy effects on sea-air CO2 fluxes in the northern Philippine Sea - Kim, Dongseon; Lee, Seon-Eun; Cho, Sosul; Kang, Dong-Jin; Park, Geun-Ha; Kang, Sok Kuh (Frontiers in Marine Science, 2022)
To determine the effects of mesoscale eddies on sea-air CO2 flux, we investigated the surface fugacity of CO2 (surface fCO2) distribution in the northern Philippine Sea, where mesoscale eddies are common. Surface fCO2 showed large spatial variations, such that values were high in the non-eddy and cyclonic eddy regions, while they were low within the anticyclonic eddy. The maximum fCO2 was observed in the non-eddy region; higher fCO2 values were observed in the area surrounding the cyclonic eddy than at the center of the cyclonic eddy. Within the cyclonic eddy, the contribution of dissolved inorganic carbon (DIC) enrichment because of upwelling was considerably offset by cooling. In the non-eddy region, the contribution of DIC enrichment from upwelling was rarely offset by cooling; thus, the maximum fCO2 was observed in the non-eddy region. Surface fCO2 showed a robust correlation with sea surface temperature (SST) within the cyclonic and anticyclonic eddies, but it did not display any correlation in the non-eddy region. Temperature was a major factor that controlled surface fCO2 in the anticyclonic eddy, but this effect was absent in the cyclonic eddy. Temperature-normalized fCO2 exhibited a clear negative relationship with SST in the cyclonic eddy and the non-eddy region, indicating that surface fCO2 was considerably affected by the upwelling of high-fCO2 deep water in both regions. Sea-air CO2 fluxes ranged from 0.011 to 9.92 mmol m-2 day-1 and all values were positive, indicating that the entire study area acted as a CO2 source during the research period. The estimated mean sea-air CO2 fluxes in the cyclonic eddy, anticyclonic eddy, and non-eddy region were 1.10 ± 0.75, 0.64 ± 0.66, and 1.42 ± 1.12 mmol m-2 day-1, respectively. The sea-air CO2 fluxes considerably varied according to eddy type; they were almost twofold higher in the cyclonic eddy than in the anticyclonic eddy. In the cyclonic eddy and non-eddy regions, upwelling caused surface fCO2 to increase, thereby increasing sea-air CO2 flux.